2009
DOI: 10.1080/14616730903135993
|View full text |Cite
|
Sign up to set email alerts
|

The role of childhood parent figure loss in the etiology of adult depression: findings from a prospective longitudinal study

Abstract: The underlying question of this study is whether childhood parental loss between infancy and sixth grade is a predictor of adult depression at age 26 years when a rating of loss severity is used. The loss rating considered the length of the separation/loss, the familiarity of substitute caregivers, the primary or supporting role of the lost parent figure, and traumatic features of the loss. The study also investigated the role of gender, developmental timing of the loss, life stress, SES, prior parental care a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
0
26
0
3
Order By: Relevance
“…More specifically, these experiences have been shown to be an important risk factor for development of later psychopathology, such as depression, post-traumatic stress disorder, anxiety, and substance abuse (Coffino, 2009; J. G. Green et al, 2010;MacMillan et al, 2001). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, these experiences have been shown to be an important risk factor for development of later psychopathology, such as depression, post-traumatic stress disorder, anxiety, and substance abuse (Coffino, 2009; J. G. Green et al, 2010;MacMillan et al, 2001). …”
mentioning
confidence: 99%
“…The current results reveal aberrant responses to positive stimuli and are consistent with the notion of persistent influence of childhood abuse on processes critical for emotional well-being and emotion control. More specifically, these experiences have been shown to be an important risk factor for development of later psychopathology, such as depression, post-traumatic stress disorder, anxiety, and substance abuse (Coffino, 2009;J. G. Green et al, 2010; MacMillan et al, 2001).…”
mentioning
confidence: 99%
“…Bu bulgu, majör depresyonun etiyolojisinde erken dönem kayıpları inceleyen araştırmalarla oldukça paralellik göstermektedir (Agid ve ark. 1999;Coffino 2009;Luecken ve Roubinov 2012;Otowa ve ark. 2014).…”
Section: Discussionunclassified
“…Bununla birlikte, kayıp ne denli erken yaşandıysa etkilerinin de o denli şiddetli olduğu bildirilmiştir. Coffino (2009), 26 yıllık izlem çalışmasının sonucunda, çocukluk döneminde yaşanan kayıpların depresyonun etiyolojisinde önemli bir etmen olduğu ve özellikle 8 yaş öncesi yaşanan kayıpların çok daha belirgin bir etkisinin olduğunu bildirmiştir. Otowa ve arkadaşları (2014) da yürüttükleri çalışmanın sonunda, kayıp yaşantısının erişkinlik döneminde içe yönelim problemleriyle ilişkili olduğunu belirtmiştir.…”
Section: Introductionunclassified
“…26 Longitudinal studies have identified some early risk factors as being predictive of later depression in general populations, including low socioeconomic status, family history of depression, family conflict, early depressive symptoms, conduct problems, substance use, delinquent behavior, and negative life events. [27][28][29][30][31][32][33][34][35] Research among predominantly White populations has also identified gender differences in risk factors with low birth weight, family composition (e.g., larger families, older parents), parental death, teen pregnancy, and childhood academic achievement problems important for women and childhood health problems and poor peer relationships important for men. 31,36,37 Because of reliance in the literature on cross-sectional work and a focus on White or racially/ethnically heterogeneous populations, it is unclear how well these risk factors predict depression among African American men and women specifically.…”
Section: Introductionmentioning
confidence: 99%